Fabrication of free-standing membranes with tunable pore structures based on the combination of electrospinning and self-assembly of block copolymers. Issue 78 (25th October 2017) - Zhou, Meimei; Wu, Yi-nan; Luo, Pingping; Lyu, Jiqiang; Mu, Dengrui; Li, Aowen; Li, Fengting; Li, Guangtao
Abstract : Polydopamine could improve interface performance of composite membranes with tunable structures which were developed by combining electrospinning and BCP self-assembly. Abstract : In this study, free-standing composite membranes with tunable pore structures are fabricated by combining electrospinning and block copolymer (BCP) self-assembly and a facile biomimetic surface modification method is employed for improvement of the interfacial interaction in the composite membranes. Firstly, polystyrene- block -poly(2-vinyl pyridine) (PS- b -P2VP) solution is drop-coated onto a electrospun PVA/SiO2 fiber mat which provides mechanical reinforcement, fabricating symmetric (thickness, 17 ± 2 μm) and asymmetric (thickness, ∼5 μm) composite membranes. The pore structures in the PS- b -P2VP matrix are realized by selectively swelling the P2VP block in hot ethanol and can be tuned by adjusting swelling time and swelling temperature. Moreover, pretreating the electrospun PVA/SiO2 fibres with adhesive polydopamine (PDA) coating improves the adherence between the BCP layer and the electrospun fibres remarkably. The results of ultrafiltration performance test show the excellent performance of the composite membrane for the immobilization and capture nanoparticles (NPs).